Implementation of the Tahfidz Program in An Effort to Build Religious Character of Students at MIS Nurul Hidayah Ketapang, South Lampung - Nisa, Choirun; Septuri, Septuri; Wachidah, Nor Rochmatul (IAIN KENDARI, 2025)
This research intends to assess the execution The Qur’an retention program developing The moral and religious disposition of students MIS Nurul Hidayah Ketapang, located in South Lampung. The tahfidz initiative aims to embed religious principles by encouraging the practice of Qur'an memorization. A qualitative approach with an evaluative method was utilized for this study. Data gathering was carried out through observations, interviews, and document reviews, together with the study participants including the madrasah principal, tahfidz instructors, and students. The data evaluation process involved phases data compacting, presentation, validation, and conclusion formulation. The findings revealed that the tahfidz program's implementation includes the planning phase, implementation, and evaluation. This program contributes to shaping students' religious character, especially in discipline, obedience to worship, and morals. The obstacles faced include time constraints, varied motivation of students, and limited teaching staff. The solutions implemented are providing motivation, parental support, and varied learning methods